Toll-Like Receptor 4/MyD88–Mediated Signaling of Hepcidin Expression Causing Brain Iron Accumulation, Oxidative Injury, and Cognitive Impairment After Intracerebral Hemorrhage. Issue 14 (4th October 2016) - Xiong, Xiao-Yi; Liu, Liang; Wang, Fa-Xiang; Yang, Yuan-Rui; Hao, Jun-Wei; Wang, Peng-Fei; Zhong, Qi; Zhou, Kai; Xiong, Ao; Zhu, Wen-Yao; Zhao, Ting; Meng, Zhao-You; et al.
Abstract : Background: Disturbance of brain iron metabolism after intracerebral hemorrhage (ICH) results in oxidative brain injury and cognition impairment. Hepcidin plays an important role in regulating iron metabolism, and we have reported that serum hepcidin is positively correlated with poor outcomes in patients with ICH. However, the roles of hepcidin in brain iron metabolism after ICH remain largely unknown. Methods: Parabiosis and ICH models combined with in vivo and in vitro experiments were used to investigate the roles of hepcidin in brain iron metabolism after ICH. Results: Increased hepcidin-25 was found in serum and primarily in astrocytes after ICH. The brain iron efflux, oxidative brain injury, and cognition impairment were improved in Hepc −/− ICH mice but aggravated by the human hepcidin-25 peptide in C57BL/6 ICH mice. Data obtained in in vitro studies showed that increased hepcidin inhibited the intracellular iron efflux of brain microvascular endothelial cells but was rescued by a hepcidin antagonist, fursultiamine. Using parabiosis ICH models also shows that increased serum hepcidin prevents brain iron efflux. In addition, Toll-like receptor 4 (TLR4)/MyD88 signaling pathway increased hepcidin expression by promoting interleukin-6 expression and signal transducer and activator of transcription 3 phosphorylation. TLR4 −/− and MyD88 −/− mice exhibited improvement in brain iron efflux at 7, 14, and 28 days after ICH, and the TLR4 antagonist (6R)-6-[ N -(2-chloro-4-fluorophenyl) sulfamoyl] cyclohex-1-ene-1–carboxylate significantly decreased brain iron levels at days 14 and 28 after ICH and improved cognition impairment at day 28. Conclusions: The results presented here show that increased hepcidin expression caused by inflammation prevents brain iron efflux via inhibition of the intracellular iron efflux of brain microvascular endothelial cells entering into circulation and aggravating oxidative brain injury and cognition impairment, which identifies a mechanistic target for muting inflammation to promote brain iron efflux and to attenuate oxidative brain injury after ICH. Abstract : Supplemental Digital Content is available in the text.